Amalgamated Theory of Microfinance, Microcredit and Empowerment - Magali, Joseph (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
This study examined the application of microfinance, microcredit and empowerment variables in Microfinance Institutions (MFI) studies. The study also evaluated the application of microfinance theory, microcredit theory and empowerment theory to determine if a single theory unifies the concepts of microfinance, microcredit and empowerment. The paper used a systematic literature review methodology and analysed 56 articles to substantiate the theories and their related variables. The review showed that most studies used the terms microfinance and microcredit interchangeably. Moreover, the study exposed that scholar’s link microfinance and microcredit to various forms of empowerment. The assessment further revealed that there were scant studies that have assessed how microfinance and microcredit influenced all empowerment categories. Moreover, studies have not integrated microfinance, microcredit and empowerment into one theory. As a result, this study proposes a unified theory that incorporates microfinance, microcredit and empowerment concepts.